2013
DOI: 10.1667/rr2946.1
|View full text |Cite
|
Sign up to set email alerts
|

Early Effects of Whole-Body56Fe Irradiation on Hippocampal Function in C57BL/6J Mice

Abstract: Relatively little is known about early irradiation effects on hippocampal function in wild-type mice. In this study, the effects of 56Fe irradiation on hippocampal function were assessed starting 2 weeks after whole-body irradiation. Compared to sham irradiation, radiation impaired novel object recognition in female and male C57BL/6J wild-type mice. There were no effects of irradiation on contextual fear conditioning or spatial memory retention in the water maze. It is possible that oxidative damage might cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 26 publications
(33 reference statements)
1
47
1
Order By: Relevance
“…(2015) have extended the results of the NOR task and complementary novel location or object in place (OiP) test to very small doses of 600 MeV/n 16 O and 48 Ti particles using 6-month-old male transgenic mice [strain Tg(Thy1-EGFP) expressing the Thy1-EGFP transgene]. These animals were significantly older than those examined by Haley et al (2013) above. The data showed substantial impairment in NOR and OiP performance 6 weeks postirradiation after 5 -30-cGy exposures depending on ion type, as shown in Figure 10.…”
Section: F Novel Object Recognitionmentioning
confidence: 98%
See 2 more Smart Citations
“…(2015) have extended the results of the NOR task and complementary novel location or object in place (OiP) test to very small doses of 600 MeV/n 16 O and 48 Ti particles using 6-month-old male transgenic mice [strain Tg(Thy1-EGFP) expressing the Thy1-EGFP transgene]. These animals were significantly older than those examined by Haley et al (2013) above. The data showed substantial impairment in NOR and OiP performance 6 weeks postirradiation after 5 -30-cGy exposures depending on ion type, as shown in Figure 10.…”
Section: F Novel Object Recognitionmentioning
confidence: 98%
“…The age at evaluation and irradiation affects the responses to charged particles (Rabin et al 2012) and X-rays (Forbes et al 2014). Sex and genotype (e.g., ApoE allele and ATM) are important variables (Acevedo et al 2008;Benice and Raber 2009;Haley et al 2012;Higuchi et al 2002;Villasana et al 2006Villasana et al , 2011Yamamoto et al 2011;Yeiser et al 2013;Johnson et al 2014;Parihar et al 2014). Additionally, observations comparing head only-, body only-, or whole body-irradiated animals demonstrate a significant role for the periphery in determining behavioral responses .…”
Section: Behavioral Effects a Overall Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The particular novel object recognition paradigm used in this study involved a 24-hour period between training and testing and relies primarily on the hippocampus and entorhinal, perirhinal, and parahippocampal cortices (Baxter, 2010). Previous studies in our laboratory have indicated that this test is particularly sensitive in detecting cognitive injury following environmental challenges (Haley et al, 2013). On day 1 (habituation), 48 hours after tMCAO, mice were placed into an open field (16″ × 16″ Kinder Scientific, Poway, CA) for 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Ground-based studies using air-breathing animals and simulated space radiations have reported radiation-induced brain injuries, including deleterious effects on dividing neuronal precursor cells in the hippocampus (13), nondividing hippocampal neurons (3, 4) and cognitive function (59). Recently published reviews suggest that acute radiation-induced oxidative stress and inflammation generate chronic reactive oxygen species that may ultimately result in late radiation-induced brain injury, including cognitive impairment (1012).…”
Section: Introductionmentioning
confidence: 99%